Literatur Review: The Effect Of Distance Learning on Students' Mathematical Problem Solving Skill - Salsabila, Ajeng Zulfa; Yuliani, Anik; Amelia, Risma (IKIP Siliwangi, 2024)
This study was intended to analyze the impact of distance learning on students' ability to solve math problems. Using the literature search method, this research was carried out by analyzing a range of types of information in qualitative and quantitative data from various texts based on previous studies. The literature exploration system uses a variety of references similar to books, exploration journals, and distance literacy operation modules that analyze students’ mathematical problem-solving skills. The results of this study validate that distance learning can affect students’ mathematical problem-solving skills when teachers use innovative methods and interactive learning media. In fact, students can develop their mathematical problem-solving skills through meaningful learning. This means that students can build their own knowledge with learning that requires independent study on the part of students so that they can construct conceptual discoveries from the material being taught. Students' mathematical problem-solving skills can also be affected by the active role played by students in distance learning. For this purpose, it is necessary for educational institutions to apply appropriate methods of learning and media that allow students to have an active role in the educational process. In addition, educational institutions must strive to provide effective and efficient communication, mentoring, and support services to students and parents.